STUDY IN INDONESIA PILOT ACADEMY, WHY NOT?: : A WEBSITE REPRESENTATION OF CRITICAL DISCOURSE ANALYSIS - Rangga Handika Putra; Adolf Andrea Marantika; Hastowohadi Hastowohadi; M. Arief Rakhman S (Journey: Journal of English Language and Pedagogy, 2023)
Indonesia Pilot Academy utilizes language as an impactful tool to affect people’s perceptions. An electronic website is becoming increasingly vital for academy and candidate cadets by employing language as information and representation. The portrayal of Indonesia Pilot Academy represents the use of linguistic representation on the website and the contribution of this to understanding the overlapping factors that reinforce academic practices within the Indonesia flight-social structure. There are unanswered questions related to the study comparing and analyzing the diverse discourses used to represent Indonesia flight academy on its website regarding social constructs (e.g., gender and race). Then, the study aims to determine website language represented as academic quality, product, and social construct.The data was taken from the website of the academy. To that end, critical discourse analysis (CDA) is utilized to describe, analyze, and interpret the textual and visual representations of the Indonesia Pilot Academy website at the local, institutional, and societal levels. What is surprising is that the academy should encourage global political involvement with promotional discourse and visual images. This finding has important implications for fostering international promotional discourse and pictures to emphasize prestige and uniqueness.